The use of poliheksametyleneguanidine (PHMG) salts in alcohol production from starch containing raw materials - Bondar, Nikolai; Shiyan, Peter; Mudrak, Tatiana; Kyrylenko, Roman (My University, 2012)
Expediency of the use of poliheksamethyleneguanidine (PHMG) salts is reasonable as the antiseptic preparation «Polidez» in alcohol production from starch-containing raw materials. In working environment its influence on the course of microbiological and biochemical processes, quality of semiproducts and alcohol was investigated and efficiency of the preparation «Polidez» for inhibition of contaminating microflora growth was confirmed.
Keywords: виробництво спирту; alcohol production; контамінуюча мікрофлора; антисептик; contaminating microflora; antiseptic; кафедра біотехнології продуктів бродіння і виноробства